Relation of anomalous F region radar echoes in the high-latitude ionosphere to auroral precipitation - H. Dahlgren; H. Dahlgren; N. M. Schlatter; N. Ivchenko; L. Roth; A. Karlsson (Annales Geophysicae, 2017)
Non-thermal echoes in incoherent scatter radar observations are occasionally seen in the high-latitude ionosphere. Such anomalous echoes are a manifestation of plasma instabilities on spatial scales matching the radar wavelength. Here we investigate the occurrence of a class of spatially localized anomalous echoes with an enhanced zero Doppler frequency feature and their relation to auroral particle precipitation. The ionization profile of the E region is used to parametrize the precipitation, with nmE and hmE being the E region peak electron density and the altitude of the peak, respectively. We find the occurrence rate of the echoes to generally increase with nmE and decrease with hmE, thereby indicating a correlation between the echoes and high-energy flux precipitation of particles with a high characteristic energy. The highest occurrence rate of > 20 % is found for hmE  =  109 km and nmE  =  1011. 9 m−3, averaged over the radar observation volume.